YANGINLA MÜCADELEDE YAPAY ZEKANIN ROLÜ - Jebril, Sjoud Wa'el Mohammad (TURAN : stratejik arastirmalar merkezi, 2025)
This research is based on a prototype application designed to examine the role of autonomous robots with artificial intelligence in fire fighting processes. Today, technological solutions developed to minimize human loss and shorten the intervention time in fire fighting are becoming increasingly important. In this context, autonomous robot systems equipped with artificial intelligence algorithms have the ability to enter risky environments without human intervention and detect, locate and extinguish fire. The prototype robot developed in the research can analyze ambient temperature and smoke density through sensors; detects and intervenes in the fire point in accordance with predetermined algorithms. The basic components of the prototype consist of mobile mobility, fire detection sensor systems, fire extinguishing mechanism and decision support artificial intelligence module. In addition, the design of the system to be remotely controlled and to make autonomous decisions in certain scenarios serves the goal of minimizing human-machine interaction. The technical data obtained show that the system is at a level that can increase its effectiveness in firefighting. This study points to the potential of artificial intelligence-based autonomous systems in firefighting technologies in the future, both in institutional firefighting units and in the field of industrial security